UMPSA enhances campus safety and well-being - Naqiah, Puaad (UMPSA, 2025)
GAMBANG, 18 January 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has increased patrols and campus security measures while advising all students to remain vigilant at the Student Residences (RP) and around the campus, particularly at night on both the Pekan and Gambang campuses.